Relationship between Body Image and Anxiety Level during Menopause at Pintu Padang District Health Center Angkola Trunk 2022 - Yetti Fauziah Silalahi (Institute of Computer Science (IOCS), 2022)
Menopause is the last menstruation, one of the psychological aspects of changebody imageDuring menopause, it is certain that menopausal women become anxious about their bodies and form a body image about how their bodies are. The purpose of this study was to determine the relationship between body image and anxiety levels during menopause at the Pintu Padang Health Center, Batang Angkola District in 2022. This type of research uses descriptive correlation and the design of this study uses a cross sectional design, the population in this study isall postmenopausal women visiting the PuskesmasPintu Padang, Batang Angkola District from January to July onin 2022 as many as 300 people.The sampling technique was purposive sampling, the number of samples was 75 people. The instrument used was a body image questionnaire sheet and an anxiety level. Data analysis was carried out with univariate and bivariate using testchi square. The results showed that the body image of the majority of respondents was high as many as 42 people (56%), the anxiety level of the majority of respondents was not anxious as many as 53 people (70.7%). The results of statistical tests with chi square values obtained. As much as 0.000 <0.05, it means that there is a relationship between body image and anxiety levels during menopause at the Pintu Padang Health Center, Batang Angkola District in 2022. The conclusion of the study is that there is a relationship between body image and anxiety levels during menopause at the Pintu Padang Health Center, Batang Angkola District in 2022. It is recommended for health workers to play an active role in increasing the knowledge of menopausal women in order to know and be aware of the changes that occur.